A physically-based analytical model to describe effective excess charge for streaming potential generation in saturated porous media - Guarracino, Luis (2016)
Different approaches have been proposed to predict streaming potentials in porous media. One approach is based on the excess charge which is effectively dragged in the medium by the water flow. Following the recent theoretical framework of Jougnot et al. (2012), we developed a physically-based analytical model to predict the effective excess charge in saturated porous media. The proposed model allows the determination of the effective excess charge as a function of pore water salinity, fractal dimension and hydraulic parameters like porosity and permeability. This new model has been successfully tested against data from the literature for different porous media. One of the main finding of this study is that it provides a mechanistic explanation to the empirical dependence between the effective excess charge and the permeability that has been found by various researchers. This model is also able to reproduce the evolution of this parameter with respect to the electrolyte concentration.